The Qur'anic Story - An Analytical Study: The story of Moses, peace be upon him, as a model - Farhan, Ban Hameed (Al-Adab Journal, 2020)
In the Holy Qur’an, God Almighty told us stories of his prophets and messengers, and what was between them and their people, and in various forms and methods in which the miracle of the Holy Qur’an appears, and among those stories is the story of Moses (peace be upon him) which is the most repeated in the Holy Qur’an, as it appeared in a hundred Thirty-six places distributed over thirty-four surahs of the Holy Qur’an (Meccan and Civil) surahs, beginning with Surah al-Baqara and ending with Surah al-Ula, and the name of a prophet in the Holy Qur’an did not have such an overwhelming share that our master Musa (peace be upon him) enjoyed, which prompted us to stand there And study it according to the analytical inductive method of PIA Mavera of the eloquence of the word, and the words of eloquence, good systems and installation.